Nurses’ Experience using Electronic Health Record: A qualitative study - Moh Heri Kurniawan; Gusrina Komara Putri (Faletehan Health Journal, 2023)
Background: Sharing information about nursing perception on the EHR is important. Nursing is a high utilizer of the EHR and without accurate and complete information in the EHR, patient safety risks increase. Aim: The objectives of this article was to explore nurses’ experience using Electronic Health Record (EHR). Method: Qualitative semi-structured interviews were conducted with 14 nurses in Jakarta hospital. Nurses were recruited from the inpatient room. The study was analyzed using Colaizzi's method of thematic analysis. Results: Nurses using EHRs in the inpatient room through the following items: 1) Data Processes; 2) barriers using EHR; and 3) nurse communication. Conclusion: Nurses are aware of the significance and standards of checking patient data, but their commitment is mitigated by some considerations including need or risk evaluation, the effect on their patient relationship, and hospital climate policies that protect the privacy of patients.